Associations of hamstring and triceps surae muscle spasticity and stance phase gait kinematics in children with spastic diplegic cerebral palsy. (5th March 2021) - Bowal, N.; Nettel-Aguirre, A.; Ursulak, G.; Condliffe, E.; Robu, I.; Goldstein, S.; Emery, C.; Ronsky, J.L.; Kuntze, G.
Abstract: Clinical decisions on interventions to improve function in children with cerebral palsy (CP) are based, in part, on hypothesized interactions amongst physical signs of CP and functional deficits. However, a knowledge gap exists regarding associations between spasticity and gait function. This study quantified associations of hamstring and triceps surae spasticity with hip, knee and ankle CP gait patterns. This is a cohort study of children and adolescents [n = 51; 31 male; 20 female; spastic diplegia; Gross Motor Function Classification System I (n = 23) and II (n = 28)] who participated in a clinical consult including gait (Motion Analysis, USA) and modified Tardieu scale (MTS) testing (hamstrings, triceps surae). Shape-based clustering was performed on stance phase sagittal hip, knee and ankle patterns using z-normalized and non-normalized data. Linear regression (R, v3.5.0, R Core Team, Austria) was conducted to assess associations between MTS measures and data clusters (α = 0.05). Shape-clustering revealed two hip and three knee and ankle clusters for z-normalized and non-normalized data. Significant associations of hamstring spasticity and joint patterns were observed for z-normalized knee clusters (CKnee A p = 0.002; CKnee B p = 0.006) and interactions amongst non-normalized hip and knee clusters (CHip A :CKnee B p = 0.033). Trends were observed for soleus spasticity and gastrocnemius range of motion angle and non-normalized ankle clusters (CAnkle B p = 0.051; CAnkle B p = 0.053 respectively). Significant associations of early knee extension and hamstring spasticity, observed using shape-clustering of z-normalized data, provide unique information that may inform the identification of individuals most likely to benefit from spasticity management and targets for spasticity management assessment.